Cardiovascular health in patients with premature ovarian insufficiency. Management of long-term consequences - Podfigurna, Agnieszka; Męczekalski, Błażej (Menopause Review/Przegląd Menopauzalny, 2018)
Cardiovascular diseases (CVDs) represent the world’s leading cause of death among women. Women with premature ovarian insufficiency (POI) may be at higher risk of cardiovascular disease, such as myocardial infarction or stroke, than women with normal menopause. The increased burden may be mediated by a worsening of cardiovascular risk factors, such as lipid profiles, with accompanying loss of ovarian function. In contrast, the increased burden may be caused by factors that precede and potentially contribute to both CVD events and ovarian decline, such as smoking. Women with X chromosome-related POI like Turner syndrome (TS) are a distinct group with unique medical needs. Regardless of the cause, women with POI may serve as an important population to target for CVD screening and prevention strategies. These strategies should include the use of CVD risk stratification tools to identify women who may benefit from lifestyle modification and pharmacological therapy to prevent CVD.